Implants for surgery - skeletal pins and wires - part 3: Kirschner skeletal wires (ISO 5838-3:1993, MOD) - Abdul Razak, Noor Hayati; Mazani, Nor Iratul Munirah; Choon, David; Goonting, Tracy E.; T, Mahadevan; Law, Chin Yee; How, Kim Chuan; Singh, Harwant; Ismail, Zulkharnain; Manickam, Thirumal; Yaakob, Mohd Amin; Mohd Yusof, Hyzan; et al. (SIRIM, 2015)
Specifies the characteristics (dimensions, ends, marking and packaging) of Kirschner wires. Material and mechanical requirements are covered by ISO 5838-1.